Konsep Pendidikan Pernikahan dalam Mempersiapkan Keluarga Sakinah Mawadah Wa Rahmah - Suhartono; Faiz Naufal (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2021)
The urgency of marriage education in building a sakinah mawaddah warahmah family is the study in this study. With this study, we hope that the public can understand all the goals, nature and wisdom of a marriage. The research used in this study uses a qualitative approach with the aim of seeking depth of analysis through analytical descriptive nature. Then it is concluded from this study that husband and wife in order to understand related problems in family life, it takes a very important provision, namely marriage education. Armed with insight into marriage education for every bride and groom who will carry out a marriage related to the intricacies of household problems. So, with the hope that family welfare will be created so that a quality generation will also be created. Because a quality generation comes from quality family relationships and quality relationships can be achieved by the knowledge of marriage education.